2022
DOI: 10.3390/diagnostics12061507
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma: Biology and Differential Diagnostic Problem

Abstract: Hodgkin lymphomas (HLs) are lymphoid neoplasms that are morphologically defined as being composed of dysplastic cells, namely, Hodgkin and Reed–Sternberg cells, in a reactive inflammatory background. The biological nature of HLs has long been unclear; however, our understanding of HL-related genetics and tumor microenvironment interactions is rapidly expanding. For example, cell surface overexpression of programmed cell death 1 ligand 1 (CD274/PD-L1) is now considered a defining feature of an HL subset, and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 159 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…TOX and TOX2 [11]. A high percentage (>75%) of tumor-infiltrating CD4 + T cells was associated with decreased freedom from treatment failure (FFTF) [12].…”
Section: Cd4 + T-cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…TOX and TOX2 [11]. A high percentage (>75%) of tumor-infiltrating CD4 + T cells was associated with decreased freedom from treatment failure (FFTF) [12].…”
Section: Cd4 + T-cellsmentioning
confidence: 99%
“…The most abundant cellular population in the TME of HL comprises CD4 + T cells, with a T-helper (T h ) phenotype, which tend to gather around HRS cells in formations called rosettes ( Figure 1 ). These cells express T cell exhaustion markers including PD-1, TOX and TOX2 [ 11 ]. A high percentage (>75%) of tumor-infiltrating CD4 + T cells was associated with decreased freedom from treatment failure (FFTF) [ 12 ].…”
Section: Overview Of Cellular Components Of Tme In Chlmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed the clinical features of patients with lymph node-reactive hyperplasia or Hodgkin's lymphoma and found no differences between the two groups. Therefore, we raised questions about why people in the same area and same living environment with the same population attributes would have different disease outcomes after infection with Epstein-Barr virus [9,10].We suspected that this difference in outcome was the result of an interaction between the body's own immune system and external antigenic stimulation, which would be related to differences in the antigens recognized by he immune cells on the one hand and the microenvironment of the tumour cells on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, they consist of large tumor cells, known as HRS cells, in a reactive inflammatory background. Recent studies have revealed that immune evasion plays a key role in the development of CHLs 6,7 . Among the multiple factors related to the immune evasion of HRS cells, the programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway is regarded as particularly important 8 .…”
mentioning
confidence: 99%